Encrypted CDMA audio network - Ortega, Alfredo A. (2014)
We present a secure LAN using sound as the physical layer for low speed applications. In particular, we show a real implementation of a point-to-point or point-to-multipoint secure acoustic network, having a short range, consuming a negligible amount of power, and requiring no specific hardware on mobile clients. The present acoustic network provides VPN-like private channels to multiple users sharing the same medium. It is based on Time-hopping CDMA, and makes use of an encrypted Bloom filter. An asymmetrical error-correction is used to supply data integrity, even in the presence of strong interference. Simulations and real experiments show its feasibility. We also provide some theoretical analysis on the principle of operation.